IAC: AN INTERACTIVE MUSIC SYSTEM - BORZA, Adrian (Studia Universitatis Babes-Bolyai Musica, 2009)
This paper aims to discuss different technical and artistic aspects of IAC software, with emphasis on interactive music system concept. Would not it be possible to create “intelligent” software that is able to “understand” the performer actions and to “follow” the score, right there on the stage? IAC facilitates the interactive composition based on programmed algorithms. The algorithms generate music structures during the ongoing performance with a MIDI keyboard connected to computer; they are designed to respond concurrently to changing pitch, intensity, and tempo.